Synthesis of Hydroxyapatite thin films on PMMA Printed Substrates - Sauñi Camposano, Yesenia Haydee (2017)
Each year millions of people suffer from bone defects resulting from trauma, tumors or bone-related injuries. Therefore there is a need to continuously develop new materials or improve the properties of the materials currently used, for bone replacement or implant applications. Polymethyl methacrylate (PMMA) has proven to be a promising alternative as a material for implants; however, there are still some limitations inherent to this material, particularly related to its surface properties. This thesis work is focused on the fabrication of hydroxyapatite (HAp) thin films on the surface of 3D printed PMMA substrates. 3D printing, particularly the Fused Deposition Modeling (FDM) technique was used to fabricate PMMA substrates with different surface porosity levels. FDM technique exhibits the potential for fabricating customized freeform structures for several applications including craniofacial reconstruction. HAp thin films were deposited by Radio Frequency Magnetron Sputtering (RFMS) and Ion Beam Sputtering (IBS) techniques, with a commercial target and an “in house” sintered target, respectively. A structural, chemical, mechanical, and morphological characterization was conducted in the generated surfaces by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and hardness and roughness measurements. The results of the XRD analysis revealed an amorphous structure for the films produced by both RFMS and IBS techniques on the PMMA substrates. The micrographs obtained by SEM showed a columnar morphology and a low density for the films produced by RFMS; the same technique revealed a structure of ridges of standing platelets with curved contours for the IBS deposited films. The amorphous structure and the morphology of the films, as well as the hardness and roughness can be propitious to improve surface properties and promote the osseointegration capabilities of PMMA. This work contributes to the basis for the development of a PMMA implant manufacturing process using 3D printing and HAp film deposition techniques, with improved osseointegration properties.